We have to solve the following set of simultaneous equations:

2x - 3y = 5 ...(1)

x - 2y = 4 ...(2)

From (2)

x - 2y = 4

=> x= 4 + 2y

Substitute in (1)

2( 4 + 2y) - 3y = 5

=> 8 + 4y -...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have to solve the following set of simultaneous equations:

2x - 3y = 5 ...(1)

x - 2y = 4 ...(2)

From (2)

x - 2y = 4

=> x= 4 + 2y

Substitute in (1)

2( 4 + 2y) - 3y = 5

=> 8 + 4y - 3y = 5

=> y = -3

x = 4 + 2y

=> x = 4 + 2*(-3)

=> x = 4 - 6

=> x = -2

**We get x = -2 and y = -3**